Health Disparities by Income in Spain before and after the Economic Crisis - Max Coveney; Pilar Garcia Gomez; Eddy Van Doorslaer; Tom Van Ourti (Tinbergen Institute, 2015)
Little is known about what the economic crisis has done to health disparities by income. We apply a decomposition method to unravel the contributions of income growth, income inequality and differential income mobility across socio-demographic groups to changes in health disparities by income in Spain using longitudinal data from the Survey of Income and Living Conditions (SILC) for the period 2004-2012. We find a modest rise in health inequality by income in Spain in the five years of economic growth prior to the start of the crisis in 2008, but a sharp fall after 2008. The drop mainly derives from the fact that loss of employment and earnings has disproportionately affected the incomes of the younger and healthier groups rather than the (mainly stable pension) incomes of the over 65s. This suggests that unequal distribution of income protection by age may reduce health inequality in the short run after an economic recession.
Keywords: D30; D63; I14; I15; 330; economic crisis; health inequality; Spain